Adrenal Hypoplasia Congenita Presenting as Congenital Adrenal Hyperplasia. (12th February 2013) - Flint, Jennifer L.; Jacobson, Jill D.
Abstract : We report on a patient with genetically confirmed adrenal hypoplasia congenita (AHC) whose presentation and laboratory abnormalities were consistent with the more common condition, congenital adrenal hyperplasia (CAH). The patient presented with failure to thrive and salt wasting. General appearance showed marked hyperpigmentation and normal male genitalia. He displayed mildly elevated 17-hydroxyprogesterone and markedly elevated 11-deoxycortisol levels at baseline and with ACTH stimulation testing. Results were consistent with 11 β -hydroxylase deficiency. He required glucocorticoids and high doses of mineralocorticoids. The marked elevation in 11-deoxycortisol directed our clinical reasoning away from a hypoplastic condition and towards a hyperplasic adrenal condition. Sequencing of the DAX1 gene (named for dosage-sensitive sex reversal (DSS) locus and the AHC locus on the X chromosome) revealed a missense mutation. A review of the literature revealed that elevated 11-deoxycortisol levels have been noted in kindreds with DAX1 mutations, but only when measured very early in life. A mouse model has recently been described that displays elevated 11-deoxycorticosterone levels and evidence for hyperplasia of the zona glomerulosa of the adrenal gland. We conclude that DAX1 testing may be considered in patients with laboratory evidence of 11 β -hydroxylase deficiency, especially in those with severe salt wasting.